(untitled) (Islamic Sciences Journal, 2026)
This study examines the origins of īlā’ (oath of abstinence) and ẓihār (wife-likeness declaration) as presented in the Prophetic Sunnah, with specific focus on the expiation (kaffārah) of ẓihār alone. It concentrates on the core legal rulings related to these concepts, rather than their secondary jurisprudential branches. Īlā’ refers to a husband’s oath to abstain from marital relations, while ẓihār denotes likening one’s wife to a female relative permanently prohibited in marriage. The study analyzes the relevant Prophetic evidences in light of the various Islamic schools of law, highlighting the role of ẓihār expiation in ensuring justice and maintaining marital balance.